Extraction of biological hydroxyapatite from bovine bone for biomedical applications - Mohd Pu"ad, N.A.S; A. Latif, A.F.; Ramli, N.D.; Muhamad, M.S; Abdullah, H.Z.; Idris, M.I.; Lee, T.C. (2020)
Current biomedical field demands intensive research on cost-effective and high availability materials to fulfil its various applications. Owing to its similar characteristic to human bone, biological hydroxyapatite (HAp) has been used as an alternative in bone replacement and implantation. In this study, biological HAp was extracted from bovine bones via calcination. Powders calcined at 700 °C and 900 °C showed the presence of HAp. The field emission scanning electron microscope (FESEM) analysis shows that the irregular morphology emerged and the size was increasing as the calcination temperature increased. By increasing the temperature of 1100 °C, β-TCP (beta-tricalcium phosphate) started to develop and influenced the ratio of Ca/P. At 900 °C, the Ca/P ratio obtained was 1.70, and closest to the theoretical ratio of Ca/P. The presence of trace elements like Ca, Mg, Sr Na, K and Zn in all samples are proved via energy-dispersive X-ray spectroscopy (EDS) analysis, and these elements help to enhance the bioactivity hence make it a good alternative in biomedical applications.